Evaluation of Potential Clinical Surrogate Markers of a Trauma Induced Alteration of Clotting Factor Activities. (28th June 2016) - Burggraf, Manuel; Payas, Arzu; Schoeneberg, Carsten; Wegner, Alexander; Kauther, Max Daniel; Lendemans, Sven
Abstract : Objective. The aim of this study was to identify routinely available clinical surrogate markers for potential clotting factor alterations following multiple trauma. Methods. In 68 patients admitted directly from the scene of the accident, all soluble clotting factors were analyzed and clinical data was collected prospectively. Ten healthy subjects served as control group. Results. Patients showed reduced activities of clotting factors II, V, VII, and X and calcium levels (all P < 0.0001 to 0.01). Levels of hemoglobin and base deficit correlated moderately to highly with the activities of a number of clotting factors. Nonsurvivors and patients who needed preclinical intubation or hemostatic therapy showed significantly reduced factor activities at admission. In contrast, factor VIII activity was markedly elevated after injury in general (P < 0.0001 ), but reduced in nonsurvivors (P < 0.05 ). Conclusions. Multiple trauma causes an early reduction of the activities of nearly all soluble clotting factors in general. Initial hemoglobin and, with certain qualifications, base deficit levels demonstrated a potential value in detecting those underlying clotting factor deficiencies. Nevertheless, their role as triggers of a hemostatic therapy as well as the observed response of factor VIII to multiple trauma and also its potential prognostic value needs further evaluation.